Influência do gás de proteção na soldagem MIG/MAG do aço inoxidável ferrítico com arames ferríticos - Ferreira Filho, Demostenes (2007)
The ferritic stainless steel has been large used, mainly in the automobile industry. One of the most important advantages of ferritic stainless steel is its lower price, if compared to austenitic stainless steel, due to absent of, nickel which is an expensive component. The ferritic stainless steel is tradittionaly welded using austenitic wires to asure good quality. Thus ferritic wires had been developed so that they can confer good quality to welds, beyond lower cost. However, there is a need of carrying out behavior studies of these wires, mainly regard to shielding gas influence, because on the MIG/MAG process, the shielding gas affects, not only the properties of the welding, but also determines the weld bead profile. Depending on the metal transfer mode, the shielding gas interacts with more or less intensity with the wire, and this interaction can lead to change in the mechanical properties and mainly in the weld bead quality. Thus, the aim of this work is to study the shielding gas influence on the ferritic stainless steel fusion zone. It was used six shielding gas composition (pure Ar, Ar+2%O2, Ar+4%O2, Ar+2%CO2, Ar+4%CO2 e Ar+8%CO2), three wires (ER430, ER430Ti e ER430LNb) and one base metal (AISI 439). The weld parameters had been determined by depositing only one weld bead in each plate and evaluating the welding current and voltage. In order to verify the shielding gas influence on the fusion zone, three weld layers were deposited, where chemical composition and microhardness were measured and formed microstructures were analyzed. It was concluded that the shielding gas has direct influence in the amount of martensite formed only for two of the used wires (ER430 and ER430Ti).